Processing Non-at-Issue Meanings of Conditional Connectives: The wenn/falls Contrast in German - Liu, Mingya (Frontiers in Psychology, 2021)
Logical connectives in natural language pose challenges to truth-conditional semantics due to pragmatics and gradience in their meaning. This paper reports on a case study of the conditional connectives (CCs) wenn/falls ‘if/when, if/in case’ in German. Using distributional evidence, I argue that wenn and falls differ in lexical pragmatics: They express different degrees of speaker commitment (i.e., credence) toward the modified antecedent proposition at the non-at-issue dimension. This contrast can be modeled using the speaker commitment scale (Giannakidou and Mari, 2016), i.e., More committed<WENN p, FALLS p>Less committed. Four experiments are reported which tested the wenn/falls contrast, as well as the summary of an additional one from Liu (2019). Experiment 1 tested the naturalness of sentences containing the CCs (wenn or falls) and conditional antecedents with varying degrees of likelihood (very likely/likely/unlikely). The starting prediction was that falls might be degraded in combination with very likely and likely events in comparison to the other conditions, which was not borne out. Experiment 2 used the forced lexical choice paradigm, testing the choice between wenn and falls in the doxastic agent’s conditional thought, depending on their belief or disbelief in the antecedent. The finding was that subjects chose falls significantly more often than wenn in the disbelief-context, and vice versa in the belief-context. Experiment 3 tested the naturalness of sentences with CCs and an additional relative clause conveying the speaker’s belief or disbelief in the antecedent. An interaction was found: While in the belief-context, wenn was rated more natural than falls, the reverse pattern was found in the disbelief-context. While the results are mixed, the combination of the findings in Experiment 2, Experiment 3 and that of Experiment 4a from Liu (2019) that falls led to lower speaker commitment ratings than wenn, provide evidence for the CC scale. Experiment 4b tested the interaction between two speaker commitment scales, namely, one of connectives (including weil ‘because’ and wenn/falls) and the other of adverbs (factive vs. non-factive, Liu, 2012). While factive and non-factive adverbs were rated equally natural for the factive causal connective, non-factive adverbs were preferred over factive ones by both CCs, with no difference between wenn and falls. This is discussed together with the result in Liu (2019), where the wenn/falls difference occurred in the absence of negative polarity items (NPIs), but disappeared in the presence of NPIs. This raises further questions on how different speaker commitment scales interact and why.